School Selection Patterns Choice and Traditional Public Schoolsthrough the Lenses of Rational Choice Theory and Behavioral Economics Theory - (:unkn) unknown (My University, 2016)
This study uses rational choice theory and behavioral economics theory to examine parent considerations when selecting an enrollment rich traditional public school (one that grew or sustained enrollment) for their child. Traditional public schools provide children general academic instruction at a school determined by the geographic boundary of their home. For many years, traditional public schools were the dominant publically funded institution for educating children. However, in the current era of school choice, parents now can select from a variety of educational options. In Milwaukee Public Schools (MPS), traditional public schools compete for students with private voucher schools, inter-district open enrollment schools, magnet/specialty schools, and both non-MPS and MPS charter schools. As a result, traditional public schools struggle to sustain student enrollment. Using the lenses of both rational choice theory and behavior economics theory, this study investigates the characteristics of schools parents considered when selecting an enrollment rich traditional public school. Results suggest that participants considered schools with high academics, regardless of income or education level. Additionally, the vast majority of participants considered three or fewer schools. This study contributes to the literature by using both rational choice theory and behavioral economics theory to understand the selection behaviors of parents who choose an enrollment rich traditional public school.
Keywords: School Choice